Panax notoginseng Promotes Repair of Colonic Microvascular Injury in Sprague-Dawley Rats with Experimental Colitis - Shiying Wang (Evidence-Based Complementary and Alternative Medicine, 2018)
To investigate the therapeutic effects of PN on intestinal inflammation and microvascular injury and its mechanisms, dextran sodium sulfate- (DSS-) or iodoacetamide- (IA-) induced rat colitis models were used. After colitis model was established, PN was orally administered for 7 days at daily dosage of 1.0 g/kg. Obvious colonic inflammation and mucosal injuries and microvessels were observed in DSS- and IA-induced colitis groups. DAI scores, serum concentrations of VEGFA121, VEGFA165, VEGFA165/VEGFA121, IL-6, and TNF-α, and expression of Rap1GAP and TSP1 proteins in the colon were significantly higher while serum concentrations of IL-4 and IL-10 and MVD in colon were significantly lower in the colitis model groups than in the normal control group. PN promoted repair of colonic mucosal injury and microvessels, attenuated inflammation, and decreased DAI scores in rats with colitis. PN also decreased the serum concentrations of VEGFA121, VEGFA165, VEGFA165/VEGFA121, IL-6, and TNF-α and increased the serum concentrations of IL-4 and IL-10, with the expression of Rap1GAP and TSP1 proteins in colonic mucosa being downregulated. The constituents of PN were identified with HPLC-DAD. To sum up, PN could promote repair of injuries of colonic mucosa and microvessels via downregulating VEGFA isoforms and inhibiting Rap1GAP/TSP1 signaling pathway.